Analisis User Experience pada Website Waste4change Menggunakan Metode Single Ease Question - Dinar Hasnan Hariri; Hannie Hannie; Intan Purnamasari (Peneliti.net, 2022)
Waste4Change is a company that provides responsible and reliable waste management solutions. According to Report Operation (Monthly Issue) data from Waste4Change, from August to November 2021, users experienced several problems when using the Waste4Change website. Based on this data, the research was conducted that aims to analyze user experience problems from the Waste4change website, design the solution design, and find out the level of convenience provided by users when testing the solution design. The research was conducted by collecting literature studies and prospective respondents first. Next, the Design Thinking stage is carried out to collect data on problems and user needs, define problems, collect solution ideas, and design the user interface to become a prototype. The last stage is a usability testing prototype with 5 respondents using the Single Ease Question method. The results of this study are that 7 user problems have been successfully defined, there are 78 user interface design pages and 8 user flows on a mobile-based prototype from the Waste4Change website that was successfully designed, and got an average SEQ value of > 5 during usability testing so that the prototype has a good level of convenience.